(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: Corona virus disease 2019(COVID-19), caused by the severe acute respiratory syndrome virus (SARS-CoV-2), heavily relies on the angiotensin-converting enzyme 2 (ACE2) receptor for cell entry. The receptor-binding domain (RBD) of the virus plays a critical role in this process and is considered a key target for neutralizing activity. The RBD can be produced efficiently and effectively to induce a neutralizing immune response. Chitosan (CS), a widely used vaccine adjuvant, shows promise as an adjuvant/carrier in vaccine delivery. Objective: To investigate the potential of CS nanoparticles (CS-NPs) as an alternative adjuvant to stimulate specific anti-RBD IgG antibody production efficiently and with reduced toxicity compared to alum. Methods: Antigens were prepared by loading RBD protein onto CS-NPs, followed by measuring the released RBD protein using high-performance liquid chromatography. Rabbits were vaccinated, and the resulting antibody response was detected using competitive enzyme linked immunosorbent assay. Results: The use of CS-NPs as an adjuvant loaded with the RBD antigen demonstrated the ability to induce a substantial titer of anti-RBD IgG antibodies when administered to rabbits over a course of three doses with two-week intervals. Comparatively, using alum as an adjuvant resulted in higher antibody titers with the same vaccination schedule. Conclusion: It was observed that CS-NPs as an adjuvant could efficiently stimulate specific anti-receptor-binding domain IgG antibodies while exhibiting less toxicity compared to alum Keywords: SARS-CoV-2, vaccine adjuvant, chitosan nanoparticles, RBD, specific IgG antibody. Citation: Mahdi FM, Abdulamir AS, Taha AA. SARS-COV-2 prevention strategy receptor binding domain loaded with chitosan nanoparticles enhance antibody production. Iraqi JMS. 2025; 23(1): 58-63. doi: 10.22578/IJMS.23.1.7